Treatment options in the young patient with Graves' disease. (7th September 2015) - Cheetham, Tim; Bliss, Richard
Summary: The treatment options in the young patient with Graves' disease are the same as in adults, namely antithyroid drug (ATD), surgery (partial or total thyroidectomy) and radioiodine. However, the emphasis and expectation is different in the young person, reflecting a range of considerations including age, pubertal status, disease natural history, likely impact of ATD on disease course and the implications of radiation exposure. New therapeutic strategies that could increase the likelihood of long‐term remission are being explored.